Schedule Performance as a Baseline for the Experimental Analysis of Coordinated Behavior: Same or Different Units of Analysis? - de Toledo, Thaís Ferro Nogara; Benvenuti, Marcelo Frota Lobato; Marques, Natália Santos; Glenn, Sigrid S. (Psychological Record, 2022)
The concept of metacontingency describes a contingent relation between the coordination of two or more individual's behavior and a selecting consequence. The concept provides several insightful avenues for experimental investigation of social behavior and behavior of people in groups. The present study explores the question of whether operant behavior of individuals and coordinated behavior of multiple individuals can be distinguished as two different conditionable units of analysis. We used rates of individual responding maintained by ratio or interval schedules of reinforcement as a baseline to evaluate the effect of consequences contingent on coordinated behavior of 27 participants in groups of three. Coordination demanded temporal spacing between responses of three participants superimposed on the variable interval or variable ratio individual reinforcement schedules. The results showed that contingency on coordinated behaviors resulted in an increased rate of coordination along with a decreased rate of responding to individual schedules. Interresponse times (IRTs) from all participants were sensitive to the coordination contingency. We discuss the need to distinguish units of analysis that describe individual behavior and units describing coordinated behavior, although these units may occur simultaneously.